Observation of hypersonic acoustics waves in a LiTaO3 crystal - BŁACHOWICZ, T.; KLESZCZEWSKI, Z. (Archives of Acoustics, 1997)
In this paper, we would like to present theoretical considerations and results of the observation of acoustic quasi-longitudinal and quasi-transverse waves in a sample of known crystalographic orientation. The Brillouin light scattering method is suitable for investigations of the acoustic properties of materials in the hypersonic range. Results of the calculation based on ultrasonic data are not in agreement with experimental hypersonic measurements. We have observed a dispersion in the velocity of the acoustic waves.